Resolution of heterogeneous charged antibody aggregates via multimodal chromatography: A comparison to conventional approaches. (19th April 2014) - Chmielowski, Rebecca A.; Meissner, Sandra; Roush, David; Linden, Thomas O.; Glowacki, Edward; Konietzko, Janelle; Nti‐Gyabaah, Joseph
<x xml:space="preserve">Abstract</x> Clearance of aggregates during protein purification is increasingly paramount as protein aggregates represent one of the major impurities in biopharmaceutical products. Aggregates, especially dimer species, represent a significant challenge for purification processing since aggregate separation coupled with high purity protein recovery can be difficult to accomplish. Biochemical characterization of the aggregate species from the hydrophobic interaction and cation exchange chromatography elution peaks revealed two different charged populations, i.e. heterogeneous charged aggregates, which led to further challenges for chromatographic removal. This paper compares multimodal versus conventional cation exchange or hydrophobic chromatography methodologies to remove heterogeneous aggregates. A full, mixed level factorial design of experiment strategy together with high throughput experimentation was employed to rapidly evaluate chromatographic parameters such as pH, conductivity, and loading. A variety of operating conditions were identified for the multimodal chromatography step, which lead to effective removal of two different charged populations of aggregate species. This multimodal chromatography step was incorporated into a monoclonal antibody purification process and successfully implemented at commercial manufacturing scale. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:636–645, 2014